Dental caries in children and COVID-19 - An interleukin association: A review of a novel concept - Sourabh Ramesh Joshi; Gowri Swaminatham Pendyala; Sachin Sarode; Gargi Sarode; Sridhar Shetty; Swati Pustake (Wolters Kluwer Medknow Publications, 2022)
COVID-19 is a pandemic throughout the world, leading to the hunger of knowledge as well as evidences regarding the corona virus which causes this disease. Interleukins are the chemokines which belong to the family of cytokines which are chemotactic in nature and cause the recruitment of cells of inflammation. In the recent COVID 19 pandemic the adverse outcomes in children, though reported less, has been related to the establishment of a cytokine storm, the components of which are common with the cytokine expression profile of Dental caries and early childhood caries in children. IL-6 levels are raised in the serum of the patients infected with COVID-19. Dental caries in children has been attributed to having its pathophysiology related in a cytokine response. Salivary IL-6 levels have been found to be elevated in children with multiple carious lesions. Hypotheses The present letter aims to propose that the multiple carious lesions can be a biomarker for the patients affected with COVID 19 due to raised IL-6 levels. Evaluation of hypotheses: The authors screened the data on COVID 19 and its association with dental caries in children. This paper is an hypotheses to highlight the importance of raised levels of IL-6 as a biomarker in the saliva of children with carious lesions and those affected with COVID-19. This communication proposes the connection between COVID-19 and dental caries through their cytokine connection to form a translational basis for recommending maintenance of oral hygiene in the COVID era. Thus every dentist must suspect every patient affected with multiple carious lesions to be a carrier of COVID-19.